2020
DOI: 10.1016/j.ecoenv.2020.110909
|View full text |Cite
|
Sign up to set email alerts
|

Larval zebrafish as an in vitro model for evaluating toxicological effects of mycotoxins

Abstract: The presence of mycotoxins in food has created concern. Mycotoxin prevalence in our environment has changed in the last few years maybe due to climatic and other environmental changes. Evidence has emerged from in vitro and in vivo models: some mycotoxins have been found to be potentially carcinogenic, embryogenically harmful, teratogenic, and to generate nephrotoxicity. The risk assessment of exposures to mycotoxins at early life stages became mandatory. In this regard, the effects of toxic compounds on zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 80 publications
(85 reference statements)
2
8
0
Order By: Relevance
“…The severity and frequency of tail deformities and yolk edema increased with dose, and the phenotypic lesions agreed with the results of Zuberi et al [57]. In contrast, in seven days post fertilization (dpf) AFB1-treated larvae, none showed phenotypic defects in previous studies [58,59].…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…The severity and frequency of tail deformities and yolk edema increased with dose, and the phenotypic lesions agreed with the results of Zuberi et al [57]. In contrast, in seven days post fertilization (dpf) AFB1-treated larvae, none showed phenotypic defects in previous studies [58,59].…”
Section: Figuresupporting
confidence: 89%
“…Significant differences were observed in deformation frequencies between the non-injected control (non-inj-c) and 4.17 nL dose (* p < 0.05). In earlier studies, the lethal effects of AFB1 on zebrafish embryos were examined in a concentration-dependent way, which aligned with dose-dependent mortality rates in the present study [57,58]. The severity and frequency of tail deformities and yolk edema increased with dose, and the phenotypic lesions agreed with the results of Zuberi et al [57].…”
Section: Figuresupporting
confidence: 89%
“…*p < 0.05, substantial alteration by comparison with the control; # p < 0.05, substantial alteration by comparison with the AFB1 administration group at counterpart concentration; ☆ p < 0.05, substantial alteration by comparison with the DON administration group at counterpart concentration. AFB1 aflatoxin B1, DON deoxynivalenol, L low concentration, M middle concentration, H high concentration studies can serve as an important reference to humans [28][29][30][31]. Consequently, embryonic zebrafish were adopted to evaluate the mixture toxic effect of AFB1 and DON in this study.…”
Section: Discussionmentioning
confidence: 99%
“…During natural hatching, the chorion is digested from the inner surface by chorionlytic enzymes (e.g., chorionase) using a biochemical mechanism followed by mechanical mechanisms (e.g., tail movements) to further help the embryo to break the remaining chorion and free itself . Studies have shown the delay in hatching after exposure to various toxins. , Mechanisms of the delay are not yet fully understood though the hardening of the outer layer of the chorion was assumed to make it difficult for the embryo to break free.…”
Section: Resultsmentioning
confidence: 99%